A Meta-analysis of Interactions Between Insect Herbivores and Plant-Parasitic Nematodes. Issue 1 (19th November 2021) - Hauri, Kayleigh C; Szendrei, Zsofia
Abstract: Insect herbivores and plant-parasitic nematodes are global, economically devastating pests that are present in nearly every crop and natural system worldwide. Although they may be spatially separated, they indirectly interact with each other by altering both plant chemical defense and nutrition. However, the outcome of these interactions is highly variable across different focal species. We performed a meta-analysis to determine how plant and nematode traits influence insect herbivore growth and reproduction, as well as nematode abundance and reproduction. We investigated how interactions between plant-parasitic nematodes and insect herbivores influence plant biomass, carbon, and nitrogen in the roots and shoots. We found no overall effect of nematodes on insect herbivores or insect herbivores on nematodes. However, while phloem-feeding insect reproduction was not affected by nematode feeding guild or plant family, chewing insect growth increased in the presence of cyst nematodes and decreased in the presence of gall nematodes. The effect of nematodes on chewing insect herbivore growth was also affected by the focal plant family. Nematode presence did not alter plant biomass when plants were exposed to aboveground insect herbivory, but carbon and nitrogen were higher in roots and nitrogen was higher in shoots of plants with nematodes and insects compared to plants with insects alone. Our results indicate that the mechanisms driving the outcome of aboveground–belowground interactions are still unclear, but those chewing insects may have more variable responses to nematode damage than phloem-feeders.